Adherence And Persistence To Antidepressant Medication During Pregnancy: Does It Differ By The Class Of Antidepressant Medication Prescribed? - Dahal, Kamala Adhikari; Patten, Scott; Lee, Sangmin (Sarah); Metcalfe, Amy (International Journal of Population Data Science, 2018)
Introduction Pregnant women are often concerned about the impact of antidepressant medication use on their pregnancy, such as congenital abnormalities. This concern may vary in a way that depends on the class of antidepressant medication prescribed. Objectives and Approach This study examined the rate of adherence and persistence to antidepressants based on the class of antidepressants prescribed during pregnancy This is a retrospective cohort study using population-based administrative data in Alberta– linking delivery record, hospitalization data, physician claims data, emergency department data, and prescription medication data. The eligible study population included women with depression who gave birth between 2012-2015, and were adherent (medication possession ratio ≥80%) to ≥ 2 consecutive antidepressant prescriptions during the preconception year (n=1,865). The rates of adherence and persistence (prescription refill gap ≤30 days) were calculated by medication class and were compared using chi-square tests. Results During pregnancy, 834 (44.7%) women completely stopped taking antidepressants. Among those taking antidepressants, the overall rate of adherence was 62.6% (95% CI: 59.4%, 65.7%). The rate differed significantly by medication class (p<0.0001), with rate of 75.1% (95% CI: 68.3%, 80.9%) for serotonin-norepinephrine inhibitors, 60.9% (95% CI: 57.2%, 64.5%) for selective serotonin reuptake inhibitors, 42.9% (95% CI: 19.9%, 69.2%) for non-selective monoamine reuptake inhibitors, and 37.5% (95% CI: 22.4%, 55.4%) for the atypical antidepressants. Similarly, 40.7%, (95% CI: 37.5, 44.0) of women were persistent to antidepressants up to the full pregnancy period – similar to the adherence pattern, the rate differed significantly by medication class. Conclusion/Implications Adherence to and persistence in using antidepressants is low during pregnancy and it varies by medication class, possessing to the worsening of depression symptoms. This could be improved by conducting more research on drug safety during pregnancy and translating research evidence into treatment decision and correcting mothers’ misperceptions towards antidepressants.